Who f(o)unded IR: American philanthropies and the discipline of International Relations in Europe. (March 2017) - Kuru, Deniz
This article aims to present a history of International Relations (IR) that looks at the role of three big American foundations (Carnegie Endowment for International Peace, Rockefeller, and Ford foundations) in the development of IR as an academic field in continental Europe. Its framework goes beyond the usual disciplinary history narratives that focus on IR's US or UK trajectories, pointing instead to American foundations' interwar and early post–World War II influence on French and German IR. The cases emphasize US foundations' interactions with European scholars and international scholarly organizations as major factors shaping IR's developmental pathways. This study offers a way to consider foundations' role in IR's gradual academic institutionalization by connecting disciplinary historical approaches to disciplinary sociology. Its sociologically conscious position underlines the significance of American philanthropies in a historical narrative and recognizes the relevance of transnational dynamics by going beyond usual emphases on ideas and national contexts.